An innovative cyclic loading device to study long term performance of offshore wind turbines. Issue 82 (March 2016) - Nikitas, G.; Vimalan, Nathan J.; Bhattacharya, S.
Abstract: One of the major uncertainties in the design of offshore wind turbines is the prediction of long term performance of the foundation i.e. the effect of millions of cycles of cyclic and dynamic loads on the foundation. This technical note presents a simple and easily scalable loading device that is able to apply millions of cycles of cyclic as well as dynamic loading to a scaled model to evaluate the long term performance. Furthermore, the device is economic and is able to replicate complex waveforms (in terms of frequency and amplitude) and also study the wind and wave misalignment aspects. The proposed test methodology may also suffice the requirements of Technology Readiness Level (TRL) Level 3–4 i.e. Experimental Proof of Concept validation as described by European Commission. Typical long term test results from two types of foundations (monopile and twisted jacket on piles) are presented to show the effectiveness of the loading device. Highlights: Innovative cyclic as well as dynamic loading device. Millions of cycles of loading can be applied to a model. Wind and wave misalignment condition can be simulated. Example application of monopile and twisted jacket.